2016
DOI: 10.1002/pmic.201500372
|View full text |Cite
|
Sign up to set email alerts
|

Multipronged functional proteomics approaches for global identification of altered cell signalling pathways in B‐cell chronic lymphocytic leukaemia

Abstract: Chronic lymphocytic leukaemia (CLL) is a malignant B cell disorder characterized by its high heterogeneity. Although genomic alterations have been broadly reported, protein studies are still in their early stages. Herein, a 224-antibody microarray has been employed to study the intracellular signalling pathways in a cohort of 14 newly diagnosed B-CLL patients as a preliminary study for further investigations. Several protein profiles were differentially identified across the cytogenetic and molecular alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The antibody arrays were blocked at 4 C with RayBiotech blocking buffer 1Â. All biotinylated samples were the incubated in the same comparable conditions as previously described by Díez et al 45 After incubation, all of the arrays were incubated with RayBiotech horseradish peroxidase (HRP)-streptavidin 1Â. The array images were acquired using a ChemiDoc MD (Bio-Rad, CA, USA) as a conventional western blot procedure at the optimized exposition.…”
Section: Protein Microarray Assaymentioning
confidence: 99%
“…The antibody arrays were blocked at 4 C with RayBiotech blocking buffer 1Â. All biotinylated samples were the incubated in the same comparable conditions as previously described by Díez et al 45 After incubation, all of the arrays were incubated with RayBiotech horseradish peroxidase (HRP)-streptavidin 1Â. The array images were acquired using a ChemiDoc MD (Bio-Rad, CA, USA) as a conventional western blot procedure at the optimized exposition.…”
Section: Protein Microarray Assaymentioning
confidence: 99%
“…Interestingly, the impact of NOTCH1 mutations appeared to be microenvironment-dependent 47. Utilizing antibody microarray-based proteomics, Díez et al compared the expression of 224 proteins in CLL samples (n=8) with or without NOTCH1 mutations 48. The study reported decreased expression of telomeric repeat-binding factor 1 (Trf-1), which is implicated in negative regulation of DNA duplication and promotion of apoptosis,49,50 protein kinase C gamma type (PKC g), which plays roles in the slow progression of CLL seen in good prognosis of the disease,43 and cyclin-dependent kinase inhibitor 2A (also know as p14arf), which inhibits cell cycle progression and incudes apoptosis 51,52.…”
Section: Proteomics Revelations Of Driver Mutations In Cllmentioning
confidence: 99%
“…Loss or mutation of TP53 were associated with poor prognosis of CLL 4. Interestingly, Díez et al reported low-expression of PKC-related proteins in CLL cells harboring alterations in TP50 48. Given the involvement of PKC proteins in the slow progression of CLL,43 their decreased expression may explain the aggressive form of the disease associated with mutated p53.…”
Section: Proteomics Revelations Of Driver Mutations In Cllmentioning
confidence: 99%
“…The newly established molecular profile can aid in ranking therapeutic agents based on their efficacy. In addition to targeted sequencing, there are several functional proteomics strategies, including protein microarrays, shotgun proteomics, multidimensional protein identification, and isotopecoded affinity tags, which can allow high-throughput screening of markers of specific B cell pathways (20).…”
Section: Considerations For Combining MCL Genomics and B Cell Signalingmentioning
confidence: 99%